2016
DOI: 10.1186/s12964-016-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Gtpbp2 is a positive regulator of Wnt signaling and maintains low levels of the Wnt negative regulator Axin

Abstract: BackgroundCanonical Wnt signals, transduced by stabilized β-catenin, play similar roles across animals in maintaining stem cell pluripotency, regulating cell differentiation, and instructing normal embryonic development. Dysregulated Wnt/β-catenin signaling causes diseases and birth defects, and a variety of regulatory processes control this pathway to ensure its proper function and integration with other signaling systems. We previously identified GTP-binding protein 2 (Gtpbp2) as a novel regulator of BMP sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…GTPBP2 mutations have been linked to neurodegeneration in humans as well (Jaberi et al 2016). However, in Xenopus embryos, GTPBP2 was reported to bind to the transcription modulator SMAD1 and take part in BMP/ SMAD1 signaling (Kirmizitas et al 2014) as well as interact with Axin and act as a positive regulator of Wnt signaling (Gillis et al 2016).…”
mentioning
confidence: 99%
“…GTPBP2 mutations have been linked to neurodegeneration in humans as well (Jaberi et al 2016). However, in Xenopus embryos, GTPBP2 was reported to bind to the transcription modulator SMAD1 and take part in BMP/ SMAD1 signaling (Kirmizitas et al 2014) as well as interact with Axin and act as a positive regulator of Wnt signaling (Gillis et al 2016).…”
mentioning
confidence: 99%
“…Wnt/β‐catenin signaling is required for polarity of embryos and maintenance of normal tissue homeostasis in Xenopus embryos, and dysregulation of Wnt/β‐catenin signaling causes diseases and birth defects 12 . Reported documents showed that knockdown of GTPBP2 disrupts activation of Wnt signaling and results in axial patterning defects and reduces induction of organizer genes in Xenopus embryos 13 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of PTK7 has been implicated as a biomarker for adenoma and CRC, and is correlated with several clinicopathological features such as TNM stage, tumor differentiation, lymph node and distant metastasis [32, 33]. Similarly, GTPBP 2 is also known as a positive regulator of the Wnt signaling pathway [34], which is involved in tumorigenesis of a wide variety of cancers including CRC. The variant in the gene APCDD1 is also shared among two families.…”
Section: Discussionmentioning
confidence: 99%